Comparison of Effect of Human Milk Fortification with Preterm Formula Powder Vs Human Milk Fortification with Human Milk Fortifier on the Growth of Very Low Birth Weight Newborns - Sidra Saleem, Sana Arshad, Athar Razzaq, Kamran Hayat, Wasif, Hassan, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: The primary aim of this scientific inquiry was to comprehensively assess how the nourishment of Very Low Birth Weight (VLBW) newborns could be improved by supplementing their diet with either human milk fortifier or preterm formula powder. Methods: A randomized controlled trial was carried out at RTEH Muzaffargarh NICU, which involved the participation of 72 preterm infants weighing between 1.2 kg and 1.6 kg at birth. The infants were randomly allocated into two groups: one received human milk fortified with preterm formula powder. In contrast, the other group received human milk fortified with a human milk fortifier. Throughout the study, weight, length, and head circumference measurements were taken for all participants. Results: There were no significant differences in gestational ages between HMF and preterm formula groups (p=0.057), nor in gender distribution (p=0.369 for males). Post-intervention, Group A experienced significant increases in birth weight (p=0.0021) and head circumference (p=0.004), but not in length. In the control group, changes in weight, head circumference, and length did not reach statistical significance. Conclusion: Human milk fortification with preterm formula powder appears to promote similar or even better growth outcomes in VLBW infants when compared to traditional fortification with human milk fortifier. However, more research is needed to confirm these findings and assess any potential long-term impacts. Keywords: Human Milk Fortification, Preterm Formula Powder, Very Low Birth Weight Infants, Growth Outcomes, Randomized Controlled Trial